Integrated Anti-Corruption Education in Teaching and Learning Process: An Overview of Pragmatics Class at Andalas University - Ike Revita (Universitas Negeri Padang, 2014)
Corruption lately becomes the prominent problem in Indonesia. This corruption occurs almost in every aspect of life. Every prospected people are of great possibility to corrupt. This is in line with the wise words that power tends to corrupt. The government has tried hard to overcome this by founding KPK (Corruption Eradication Commission). The action against corruption ideally is not only done by KPK but also every people in Indonesia, including educational institution. As an institution of creating the characterized agent, the educational institution is responsible to educate the students to be anti-corruptor. One simple way is by implementing it in the teaching and learning process. This writing is aimed at describing some tricks of integrating anti-corruption value in teaching and learning process. The research is conducted in Pragmatics class at English Department Andalas University. Pragmatics is a compulsory subject offered to English Department Students at Andalas University. The research is qualitatively and descriptively done. By applying the concept of long- life learning by Ramsden (1992), it is found some ways of integrating the value of anti-corruption in teaching and learning process. They are in (1) class action–course contracts reflecting anti-corruption; (2) evaluation–honest and discipline; and (3) assessment–transparency. These all are designed, written, and socialized in syllabus.